Cancer Metastasis, Molecular and Cellular Mechanisms and Clinical Intervention - Jiang, Wen G.; Mansel, Robert E. (Cancer Metastasis - Biology and Treatment, 2000)
This book covers the molecular and cellular aspects of cancer metastasis, and discusses the clinical aspect of micro- and macro-metastases, which result in the death of the majority of patients with cancer. The current edition attempts to examine the current status of the basic scientific and clinical research in the area, and is a very useful reference for clinicians, oncologists, and biologists. It is intended for undergraduates as well as postgraduates in the area of medicine, oncology, and cancer biology